New Method of Measure Thermal Conductivity of Nanofluids - Hosseini, Seyed Sharafaldin (2009)
Work on applications of nanofluids can be restricted due to unavailable conductivity meter for nanofluids in the market. This study is concerned with design and development of a conductivity meter for nanofluids for temperature range of 20°C – 50 °C for copper oxide and alumina with distilled water as base fluid. This temperature range is in accordance with ordinary thermal applications and our empirical limitations. The meter is comprised of the components such as a plastic water bath, an electrical heater, some thermometers, an electrical motor, a fan, an electrical transformer, and a 100 ml Pyrex beaker. In this method both conduction and convection were considered to measure the thermal conductivity of moving fluids. Calibration and verification of the equipment by using distilled water showed a significant agreement to conductivity standard value of ASTM standard. Results showed that CuO-distilled water has higher thermal properties than aluminadistilled water, and that means particles with higher thermal conductivity make higher conductive nanofluids. For example percentage of thermal conductivity rising for 2%mass CuO-distilled water in 45°C is equal to 33.5% but this value for alumina is equal to 26%. Among our nanofluids 4% mass particle concentration of CuO-distilled water gave the highest conductivity value and least is 1 mass% particle concentration of alumina-distilled water. Result also showed that this meter can give the conductivity value of 0.001 decimal places. Finally it can be concluded that nanofluids can consider as new generation of thermal fluid with higher thermal conductivity than traditional thermal fluids. They also can increase the efficiency of thermal equipments.